Effect of Sc Addition on the Microstructure and Wear Properties of A356 Alloy and A356–TiB2in Situ Composite - A. K., Prasada Rao; S. L., Pramod; B. S., Murty; Srinivasa R., Bakshi (Elsevier, 2015)
In this study, the effect of Sc addition on the grain refinement, modification of the eutectic Si, mechanical and wear properties of A356 and A356–10 wt% TiB2in situ composite has been investigated. The A356–10 wt% TiB2 composites were prepared by an in situ reaction between K2TiF6 and KBF4 salts, which are added in proper stoichiometric ratio to form TiB2 in the A356 alloy melt at a temperature of 1073 K (800 °C). Al–2 wt% Sc master alloy was added to A356 and A356–10 wt% TiB2 melt to introduce 0.2 and 0.4 wt% Sc in the alloy and the composite. Addition of Sc reduced the secondary dendrite arms spacing (SDAS) by 50% and changed the Si morphology from needle-like to fine spheroidal particles. Microstructure of Sc modified alloys which were cast for different holding times of 0, 30, 60 and 120 min indicated that there was no fading or poisoning effect on the SDAS and eutectic Si morphology. Hardness was found to increase due to addition of Sc and TiB2. Pin-on-disk wear tests indicated that Sc addition increase the wear resistance of A356 alloy but reduced the wear resistance of A356–TiB2 composite.